Examining the Dual Effects of Incentive Type and Distribution Timing on Employee Performance in Indonesian Corporate Settings - Halim, Hartanto; Sulaiman, Eman; Herlina, Ellin (UIN Sunan Gunung Djati, 2026)
This study aims to analyze and compare the effectiveness of incentive schemes based on their type (monetary vs. non-monetary) and timing of distribution (monthly vs. quarterly) in enhancing employee performance. The research is motivated by the recurring challenge that poorly designed incentive systems often fail to motivate employees and may even trigger dissatisfaction and turnover. Using a quantitative approach, the study employed a Likert-scale questionnaire that was validated and proven reliable (Cronbach’s Alpha = 0.872). The sample comprised 50 employees of Company X in Jakarta selected through purposive sampling. Data were analyzed using independent t-test, one-way ANOVA, and multiple linear regression to identify the relative effects of each factor. The results show that monetary incentives are perceived as significantly more effective than non-monetary ones in improving motivation and productivity (β = 0.440; p < 0.001). Likewise, the timeliness of incentive distribution—particularly when provided within one month after achieving the target—has a positive and significant impact on performance (β = 0.325; p = 0.005). The regression model demonstrates that the combination of monetary incentives and monthly distribution yields the strongest performance enhancement, explaining 51.5% of performance variation (R² = 0.515). These findings confirm that both the form and timing of rewards act as complementary drivers of employee commitment and effort. Practically, the study underscores the importance of integrated incentive design that balances financial and non-financial elements, ensures timely delivery, and maintains transparency to reinforce perceptions of fairness and trust. Theoretically, it contributes to strategic human resource management by contextualizing expectancy theory and equity theory within the Indonesian corporate setting. The originality of this study lies in its dual-dimensional analysis of incentive type and timing, a combination rarely examined simultaneously in prior HRM research in Indonesia.